PHOTODYNAMIC THERAPY: NEW LIGHT IN MEDICINE WORLD - Venny Santosa; Leenawaty Limantara (Universitas Gadjah Mada, 2008)
Photodynamic therapy (PDT) is a considerably new kind of photochemotherapeutic treatment in medical field. It combines the use of three components, which are a photosensitizer, light and oxygen. Photosensitizer is a compound activated by light. The application can be oral, topical or intravenous. It usually member of porphyrin group with ampiphilic characteristics. Photosensitizer can be of generation I, II or III, each generation step develops more specificity, selectivity and deeper tissue application. This review will discuss photosensitizer development consecutively, with its benefit and lackness. The light used is usually on red region, while the oxygen is involved in reactive oxygen species generation. Its mechanism action can go through either in type I or type II reaction. This kind of therapy is usually being used in oncology, especially in superficial and in-lining cancers, dermatology and ophthalmology field. This therapy can be safely given to patients with complication and has distinct advantages compare with other treatment such as chemotherapy and surgery. It also considerably has lesser side effects and risks. Broader application is being developed through various experiments and photosensitizer modification.